Influence Analysis of The Factors Determining Consumer Decisions on The Marketing Performance of J&T Express in Pontianak - Andry Lindi Lim (Jurnal Indonesia Sosial Sains, 2024)
Digital technology, such as e-commerce, has changed the way people live by providing convenience, speed, comfort and efficiency. Freight forwarding services are vital in online transactions to deliver goods from sellers to buyers.  The purpose of this study was conducted to determine the effect of customer orientation, promotional attractiveness, and competitive pricing on marketing performance. This research method uses the causality method which aims to test how much the cause-and-effect relationship between the independent variable and the dependent variable is. The population of this study were consumers totaling 13,577, from 2018-2023, and a sample of 100 respondents. The data analysis technique uses quantitative data analysis and uses a range scale measurement. The results of simultaneous testing (F test) indicate that customer orientation, promotional attractiveness, and competitive prices have a significant effect on marketing performance. The results of persial testing (t test) show that customer orientation, promotional attractiveness, and competitive prices have a significant effect on marketing performance.